Mermaids are real! - Hatam, Holly (New York, NY : Random House, 2020)
"Treasure and coral and song--that's what mermaids are made of. Take a peek into their secret magical world!" -- Page [4] cover.
A whimsical glimpse into the magical world of mermaids describes how they are made of song, pearls, coral, and daydreams; how they love to play and dance in the ocean; and how they love veggies, especially seaweed.
On board pages.
Cover title.
Keywords: Board books; Mermaids -- Juvenile fiction; Magic -- Juvenile fiction; Board books; Mermaids -- Fiction; Board books; Magic; Mermaids; Mermaids and mermen -- Juvenile fiction; Magic -- Juvenile fiction; Mermaids and mermen -- Fiction; Magic -- Fiction; Picture books; Board books; Fiction; Juvenile works; Picture books